Preparing Undergraduate Students for Mentorship With Youth of Marginalized Identities: A Model for Food Systems Education - Livstrom, Illana; Roehrig, Gillian; Smith, Amy; Rogers, Mary (Frontiers in Sustainable Food Systems, 2022)
Undergraduate programs in sustainability and food systems studies increasingly recognize the importance of building equity competencies for students within these programs. Experiential learning opportunities in these programs often place students in internships or service learning in racially, ethnically, and socioeconomically diverse communities. Many community-based organizations focus on youth development and empowerment through mentorship. Learning in these contexts can be mutually beneficial for mentors, youth and community organizations working in partnership toward a shared goal. Intentional preparation of mentors for these experiences is germane, particularly when mentoring youth with marginalized identities. Mentoring in the U.S. historically and currently rests on deficit-oriented discourses that position youth of marginalized identities as needing help, and that help is often provided by white and privileged saviors. Many programs intentionally or unintentionally employ assimilation models with white middle/upper class ideologies and expectations for success, which further lift dominant identities while marginalizing the youth of focus. These models also displace focus from systemic inequities, while placing blame on individuals. Building equity-based competencies with undergraduate mentors is necessary to avoid these downfalls that perpetuate harmful practices and discourses. Through intergenerational mentorship and urban agriculture, GNM works to advance environmental, social and racial justice in North Minneapolis. The GNM partnership was originally initiated by community members that wished to build pathways to the University and workforce for youth through agriculture, food systems, and natural resource sciences. In this study, we highlight results from our experience preparing undergraduate mentors through Growing North Minneapolis, an urban agriculture program and community-driven collaboration between North Minneapolis community elders and the University of Minnesota, focusing on youth and their communities. This case study serves as a model for building equity-based competencies in undergraduate programs. Our findings highlight (1) how the experience of collaborative mentoring in community-based internship for youth of marginalized identities can support the growth of undergraduate mentors and (2) how undergraduate mentors can be prepared to work with communities and youth of marginalized identities in critical ways within an equity-based framework.